2015
DOI: 10.1155/2015/539841
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Pathway Was Involved in Regulating Programmed Cell Death 1 Expression during Sepsis‐Induced Immunosuppression

Abstract: Programmed cell death 1 (PD-1) plays an important pathologic role in sepsis-induced immunosuppression. However, whether PD-1 overexpression occurs early during septic shock is unknown and its regulation mechanism is also unknown. Our study investigated the expressions of PD-1/programmed death-ligand 1 (PD-L1) on immune cells in peripheral blood from the early-stage septic shock patients. We found that both PD-1 and PD-L1 showed increased expressions on the CD4+ T cells and monocytes. It indicated that PD-1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Importantly, by inhibiting the Notch signaling pathway in a lipopolysaccharide‐tolerant THP1 cell model, Pan et al . found that the Notch signaling pathway was involved in up‐regulating PD‐L1 expression in monocytes . On the other hand, the role of OX40L in the induction of Treg cells is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, by inhibiting the Notch signaling pathway in a lipopolysaccharide‐tolerant THP1 cell model, Pan et al . found that the Notch signaling pathway was involved in up‐regulating PD‐L1 expression in monocytes . On the other hand, the role of OX40L in the induction of Treg cells is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…17 Importantly, by inhibiting the Notch signaling pathway in a lipopolysaccharide-tolerant THP1 cell model, Pan et al found that the Notch signaling pathway was involved in up-regulating PD-L1 expression in monocytes. 48 On the other hand, the role of OX40L in the induction of Treg cells is controversial. Although a study by Gopisetty et al demonstrated that OX40L-and Jagged1-induced co-signaling by BMDCs was required for Treg cell expansion, 25 most reports supported up-regulation of OX40L on DCs being implicated in the induction of Th2 responses and allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating this, the Notch intracellular domain and the recombination signal binding protein for immunoglobulin kappa J (RBPJκ), two critical components of the Notch signaling pathway, were bound to the Pdcd1 locus within six hours of in vitro peptide-mediated TCR stimulation (Figure 1b). Similarly, in T cells of patients experiencing sepsis-induced immunosuppression, Notch pathway activation also correlated with PD-1 expression (74). In a model using IL-10 and LPS to cause sepsis-induced immunosuppression in CD4 T cells and macrophages, inhibition of Notch signaling again reduced PD-1 expression.…”
Section: Transcription Factors Inducing Acute Pd-1 Expressionmentioning
confidence: 99%
“…Similar relationship between Notch pathway and PD-1, a receptor for PD-L1 on lymphocytes, has been reported previously in septic shock patients, where inhibition of Notch pathway significantly decreased PD-1 expressions. 27 Moreover, it has been shown that Notch is required for PD-1 upregulation during CD8 + T-cell activation. 28 Likewise, PD-L1 was upregulated through a notch in human primary monocytes.…”
Section: Discussionmentioning
confidence: 99%